Biomedical Informatics in the Desert - A New and Unique Program at Arizona State University - Greenes, R. A.; Panchanathan, S.; Patel, V.; Silverman, H.; Shortliffe, E. H. (Yearbook of Medical Informatics, 2008)
Objectives A new academic Biomedical Informatics (BMI) Program in Phoenix, Arizona, embodies a unique organizational structure to draw on the strengths of a computer science and informatics school and the biomedical and clinical strengths of a college of medicine, in an effort to infuse informatics approaches broadly.MethodsThe program reflects a partnership of two state universities that situates the Arizona State University (ASU) Department of BMI on a new downtown Phoenix Biomedical Campus with the University of Arizona (UA) College of Medicine in partnership with ASU (COMPHX). Plans call for development of faculty and expertise in the four major subdomains of BMI, as well as in various cross-cutting capabilities.Results Coming into existence in a state that is investing significantly in biomedical science and technology, BMI has already developed Masters and PhD degree programs, is working with COMPHX to integrate informatics intensively into the education of the medical students, and has been authorized to plan for an undergraduate program in BMI. Reflecting the statewide emphasis on the biomedical and health sector, the growing faculty are engaged in a number of research partnerships and collaborative centers.Conclusions As one of the newest academic BMI programs is taking shape in Arizona, it is embarking on a wide-ranging educational program and a broad research agenda that are now in their earliest stages.
Keywords: Biomedical informatics; education; academic departments; training